Media Augmented Reality Berbasis Permainan Tradisional untukMeningkatkan Literasi Numerasi Siswa - Putri, Iin Karmila; Nur Asri, Muh Fitra; Anas, Aswar (Jurnal Bumigora Information Technology (BITe), 2025)
Background: Elementary school learning still faces challenges in providing meaningful, contextual learning experiencesthat foster students’ reasoning skills.Objective: This study aimed to design and develop an augmented reality–based mathematics learning medium thatintegrates traditional Luwu games, Madende and Maguli, to enhance elementary students’ numeracy literacy.Methods: A needs analysis was conducted through classroom observations, teacher interviews, and student questionnaires.Numeracy elements were identified from the rules of the traditional games. The learning media were designed andimplemented using Unity with image-based tracking technology. Expert validation and a limited trial were conducted with25 fifth-grade students.Result: The developed product was rated as highly feasible, with an average validity score of 85%. Students’ mean scoresincreased from 62.4 to 80.6, yielding a normalized gain score of 0.48. User responses were positive, and teachers assessedthe media as suitable for classroom use.Conclusion: The integration of Augmented Reality with local cultural contexts supports numeracy learning and has thepotential for broader adoption following performance optimization and further comparative testing.